How to create an investment portfolio of an individual investor - Pustaj, Marek (2010)
The goal of the thesis is to point out the necessity of the financial and investment planning, to describe and explain the basic rules and principles of the financial and investment planning and then create an investment portfolio of an individual investor. The thesis is divided into four main chapters, I start with a shorter chapter about inflation. Next chapter is dedicated to the entire process of financial planning. From the analysis, through a financial plan to the implementation and revision of the plan. Managing our finances we should follow mentioned rules and principles. The most relevant part of the financial plan is investment plan. So next chapter is dedicated to the investment planning. I make clear the basics of investment theory here. The last chapter is practical, it is the example of creating an investment portfolio of an individual investor.